2022
DOI: 10.1002/mds.29171
|View full text |Cite
|
Sign up to set email alerts
|

Serum MicroRNAs Predict Isolated Rapid Eye Movement Sleep Behavior Disorder and Lewy Body Diseases

Abstract: Background Isolated rapid eye movement sleep behavior disorder (IRBD) is a well‐established clinical risk factor for Lewy body diseases (LBDs), such as Parkinson's disease (PD) and dementia with Lewy bodies (DLB). Objective To elucidate whether serum microRNA (miRNA) deregulation in IRBD can antedate the diagnosis of LBD by performing a longitudinal study in different progression stages of IRBD before and after LBD diagnosis and assessing the predictive performance of differentially expressed miRNAs by machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Similarly, two earlier studies showed distinct miRNA fingerprints in iPD and monogenic PD patients with LRRK2, SNCA, or GBA mutations 31,42 . In addition, miR-19b-3p and miR-29c-3p were previously associated with iPD 25,26,29,30,43,44 or idiopathic RBD 27,28 , and were also deregulated in our study only in iPD but not in G2019S carriers. Altogether, these results align with previous findings 31,42 indicating group-specific miRNA deregulation between iPD and L2PD and an overall greater miRNA deregulation effect in iPD than in L2PD, which is compliant with the complex multifactorial etiology of iPD 45,46 .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Similarly, two earlier studies showed distinct miRNA fingerprints in iPD and monogenic PD patients with LRRK2, SNCA, or GBA mutations 31,42 . In addition, miR-19b-3p and miR-29c-3p were previously associated with iPD 25,26,29,30,43,44 or idiopathic RBD 27,28 , and were also deregulated in our study only in iPD but not in G2019S carriers. Altogether, these results align with previous findings 31,42 indicating group-specific miRNA deregulation between iPD and L2PD and an overall greater miRNA deregulation effect in iPD than in L2PD, which is compliant with the complex multifactorial etiology of iPD 45,46 .…”
Section: Discussionsupporting
confidence: 59%
“…After discarding commercially available assays which did not amplify at a minimum quality level in serum samples, by real-time quantitative PCR (RT-qPCR) we tested a total of 12 candidate miRNAs. These included 10 candidate DEmiR detected by the array (miR-122-5p, miR-16-5p, miR-185-5p, miR-19b-3p, miR-22-3p, miR-221-3p, miR-29c-3p, miR-3196, miR-4505, miR-451a, miR-6125 and miR-8069), and 2 additional candidate miRNA earlier reported in iPD (miR-29c-3p) 25,27 or well-established PD prodromal stages (idiopathic RBD) (miR-451a) 28 . Among the candidate miRNAs selected from the array, miR-185-5p, miR-6125, miR-3196, miR-4505, and miR-22-3p were detected in more than one comparison (Supplementary Table 1), and miR-19b-3p and miR-221-3p were previously reported as deregulated miRNAs in PD 25 and idiopathic RBD 28 .…”
Section: Rt-qpcr Mirna Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Four independent miRNA microarrays revealed several dysregulated miRNAs in MSA patients: miR-19b-3p, miR-25-3p and miR-92a-3p [ 18 , 112 , 113 , 114 , 115 , 119 ]. miR-19b-3p has been reported as a biomarker of PD in several studies [ 140 , 141 ]. Interestingly, both miR-25-3p and miR-19b-3p have been detected in the serum of patients with an isolated form of REM sleep behavior disorder, representing the prodromal state of the α-synucleinopathies, suggesting that these miRNAs could be potential prognostic biomarkers for α-synucleinopathies [ 142 ].…”
Section: The Association Of Mirna Dysregulation and Msa Pathologymentioning
confidence: 99%
“…For instance, a recent study found sustained deregulation of 12 miRNAs across the RBD continuum. 18 We ourselves investigated the expression of miRNAs in routine colonic biopsies from PD cases by miRNA sequencing (miRNA-seq) and found several differentially expressed submucosa-enriched miRNAs, with hsa-miRNA-486-5p having the highest effect size for PD. 19 Because colonic biopsies are less well suited for routine diagnostics, we here tested the diagnostic value of the eight most promising candidate miRNAs from our previous report in buccal (oral) and nasal swabs in PD and iRBD cases and in healthy controls.…”
Section: Introductionmentioning
confidence: 99%